Regulation of pyroptosis by natural products in atherosclerosis: mechanisms and therapeutic potential - Shi, Na; Wei, Lai; Wang, He; Sun, Shude; Yang, Jianfei; Zhou, Yabin (Frontiers in Pharmacology, 2025)
Pyroptosis, a proinflammatory form of programmed cell death characterized by inflammasome activation and gasdermin-mediated membrane pore formation, has been recognized as a critical contributor to the initiation and progression of atherosclerosis (AS). Increasing evidence indicates that pyroptosis accelerates plaque formation and rupture by promoting endothelial dysfunction, vascular smooth muscle cell loss, and destabilization of macrophage-derived foam cells. Given its pivotal role in AS pathogenesis, modulation of pyroptotic signaling pathways is considered a highly promising therapeutic strategy. Natural products derived from medicinal plants and dietary sources possess multiple biological activities, including antioxidant, anti-inflammatory, and lipid-regulating effects, and their potential to target pyroptosis in cardiovascular diseases has attracted growing attention in recent years. This review systematically summarizes current advances in understanding the regulatory effects of natural products on pyroptosis in AS. Representative compounds, including polyphenols, flavonoids, saponins, and alkaloids, have been shown in AS animal models to inhibit inflammasome assembly, block gasdermin cleavage, and restore vascular homeostasis. This review focuses on elucidating the mechanisms and therapeutic potential of natural products in regulating pyroptosis in AS, aiming to provide a reference for their application in AS treatment and to lay a foundation for the development of effective new drugs for AS prevention and management.